An overview of cutaneous T cell lymphomas - Bagherani, Nooshin (F1000Res, 2016)
Cutaneous T cell lymphomas (CTCLs) are a heterogeneous group of extranodal non-Hodgkin’s lymphomas that are characterized by a cutaneous infiltration of malignant monoclonal T lymphocytes. They typically afflict adults with a median age of 55 to 60 years, and the annual incidence is about 0.5 per 100,000. Mycosis fungoides, Sézary syndrome, and primary cutaneous peripheral T cell lymphomas not otherwise specified are the most important subtypes of CTCL. CTCL is a complicated concept in terms of etiopathogenesis, diagnosis, therapy, and prognosis. Herein, we summarize advances which have been achieved in these fields.